Regional climate simulation of present day temperature over India using RegCM3: Evaluation and analysis of model performance - MAURYA, R. K. S.; SINGH, G. P.; CHOUDHARY, U. K.; BHAN, S. C. (MAUSAM, 2017)
The study has focused on the evaluation of model performance on simulated air temperature at surface and mid atmospheric level over the Indian subcontinent using a Regional Climate Model version 3 (RegCM3). The model is used at 40 km horizontal resolution over the domain approximately 58° E-102.5° E & 5° N-40° N for the period of 1982-2006. The temperatures at lower troposphere (850 hPa) and mid tropospheric level (500 hPa) have been simulated with reanalysis dataset of the National Centre for Environmental Prediction (NCEP). Various statistical measures namely Mean Bias Error (MBE), Root Mean Square Error (RMSE), Mean Percentage Error (MPE) and Correlation Coefficients (CCs) has been used to test the model results. It has been found that the RegCM3 is able to capture the main features of the observed mean surface climate and also patterns of surface and mid-level air temperatures over India. The model showed that cold biases were -4.29 °C (16.4%) at the lower troposphere, but insignificant at the mid atmospheric level in comparison to the NCEP dataset. The air temperature was well captured at mid tropospheric level. The CC between RegCM3 and NCEP is significantly high (0.82) over India in respect of annual surface air temperature (SAT). The trends of observed SAT were found to be significant increased by 0.32 °C with NCEP and 0.40 °C with RegCM3 over India. The annual SAT of cold biases ranging between -2 °C to -5 °C was found over major parts of India while cold biases of above -5 °C was found in the regions of low elevation or valley regions and below -2 °C in the mountainous regions. The analysis of annual and seasonal trends of maximum air temperature (Tmax), minimum air temperature (Tmin) and average air temperature (Tave) showed that the increasing trend was found over the Indo-Gangetic plain, Western Himalayas (WH) and North East India (NEI) in all seasons while decreasing trend over the North Central India (NCI) in the summer season and over the state of Gujarat in the monsoon season. The RegCM3 showed higher Water Vapour Mixing Ratio (WVMR) at the lower troposphere resulting more cooling at surface rather than at mid tropospheric level.